PEPFAR support of alcohol–HIV prevention activities in Namibia and Botswana: a framework for investigation, implementation and evaluation. (26th January 2016) - Glenshaw, M.; Deluca, N.; Adams, R.; Parry, C.; Fritz, K.; Du Preez, V.; Voetsch, K.; Lekone, P.; Seth, P.; Bachanas, P.; Grillo, M.; Kresina, T. F.; et al.
Abstract : Background: The association between harmful use of alcohol and HIV infection is well documented. To address this dual epidemic, the US President's Emergency Plan for AIDS Relief (PEPFAR) developed and implemented a multi-pronged approach primarily in Namibia and Botswana. We present the approach and preliminary results of the public health investigative and programmatic activities designed, initiated and supported by PEPFAR to combat the harmful use of alcohol and its association as a driver of HIV morbidity and mortality from 2008 to 2013. Approach: PEPFAR supported comprehensive alcohol programming using a matrix model approach that combined the socio-ecological framework and the Alcohol Misuse Prevention and Intervention Continuum. This structure enabled seven component objectives: (1) to quantify harmful use of alcohol through rapid assessments; (2) to develop and evaluate alcohol-based interventions; (3) to promote screening programs and alcohol abuse resource services; (4) to support stakeholder networks; (5) to support policy interventions and (6) structural interventions; and (7) to institutionalize universal prevention messages. Discussion: Targeted PEPFAR support for alcohol activities resulted in several projects to address harmful alcohol use and HIV. Components are graphically conceptualized within the matrix model, demonstrating the intersections between primary, secondary and tertiary prevention activities and individual, interpersonal, community, and societal factors. Key initiative successes included leveraging alcohol harm prevention activities that enabled projects to be piloted in healthcare settings, schools, communities, and alcohol outlets. Primary challenges included the complexity of multi-sectorial programming, varying degrees of political will, and difficulties monitoring outcomes over the short duration of the program.